The Incidence and Outcomes of Pancreatectomy in Patients with Metastatic Pancreatic Adenocarcinoma - McKenzie, Shaun; Mailey, Brian; Artinyan, Avo; Kim, Joseph; Ellenhorn, Joshua D I (JOP. Journal of the Pancreas, 2010)
Context Despite current management guidelines, patients with metastatic pancreatic cancer continue to undergo pancreatic resection. Objective Our objective was to determine the incidence and outcomes of pancreatic resection in the setting of known metastatic disease. Design Using the Los Angeles County Cancer Surveillance Program, patients with pancreatic adenocarcinoma who underwent pancreatic resection with known M1 (AJCC stage IV) metastatic disease between the years 1988-2006 were assessed. Setting Large population based database query. Patients Patients with biopsy proven M1 pancreatic adenocarcinoma. Interventions Pancreatic resection, systemic chemotherapy, radiation therapy. Main outcome measure Overall survival. Results Of 8,549 patients with pancreatic adenocarcinoma from Cancer Surveillance Program, 54% (n=4,649) initially presented with M1 disease. Within this M1 cohort, 2% (n=92) of patients underwent pancreatic resection and formed our final study cohort; these patients comprised 7% of the overall number of pancreatic resections performed for pancreatic adenocarcinoma during the study period. Only 35% (n=32) of the study cohort received adjuvant chemotherapy; and 13% (n=12) received adjuvant radiotherapy. Median survival for the study cohort was 6.3 months. Surgery provided no survival benefit over chemotherapy in patients with M1 disease and was associated with an 18% 30-day mortality. Conclusion A large number of patients from Los Angeles County have undergone pancreatic resection despite the presence of known metastatic disease. Patient survival remains abysmal in this setting and these results are likely a microcosm of the surgical management of metastatic pancreatic cancer in the USA. These results highlight the necessary efforts to maintain appropriate standards of care in the management of pancreatic cancer. Image: Survival analysis of M1 patients with pancreatic adenocarcinoma.